IMPOLITENESS STRATEGIES OLEH WARGANET PADA UNGGAHAN INSTAGRAM TERKAIT KEBIJAKAN PEMERINTAH MENGENAI TES PCR - I Made Astu Mahayana; Dewa Ayu Dyah Pertiwi Putri; I Gede Sandi Haris Saskara; Made Sani Damayanthi Muliawan (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
This study aims to analyze the impoliteness strategies used by netizens on Instagram uploads related to government policies regarding PCR tests. One of the causes of the emergence of impoliteness is caused by government policies that are not in favor of the people in terms of decision making during the pandemic, one of which is the policy of implementing PCR. This research used a descriptive qualitative approach. The data from this study are impolite strategies that are sourced from netizen comments on Instagram uploads related to government policies regarding PCR tests. In data collection, additional instruments were used, namely gadgets, notebooks, and stationery. Based on the results of the study, it was found that negative impoliteness became the dominant strategy used by netizens in the comments column. This shows that many people are disappointed and dissatisfied with the government's new policy regarding PCR.